Peranan Kepala Sekolah dalam Meningkatkan Ru>hul Mudarris (Jiwa Guru) - Ach. Nurholis Majid; Hilimiah Isykirati; Abd. Qadir Jailani (Maharot : Journal of Islamic Education, 2021)
This study aims to describe and find two things (1) the concept of ru>hul mudarris (teacher's soul) at Tahfidh Putri Al-Amien Prenduan Middle School (2) the role of the principal in increasing ru>hul mudarris (teacher's soul) at Tahfidh Putri Al Middle School Al-Amien Prenduan. This research uses a descriptive qualitative approach with a case study type. The data were collected through interviews, observation, and documentation. To analyze the data that has been collected, interactive data reduction, data display, and conclusion are drawn. This study concludes two essential things. First, the concept of ru>hul mudarris (teacher's soul) in SMP Tahfidh Putri Al-Amien Prenduan is the concept of ru>hul mudarris (teacher's soul) based on adab or ethics, the concept of ru>hul mudarris (teacher's soul) is skill-based ruhiyah, and the concept of ru>hul mudarris (teacher soul) based on the Qur'anic soul. Second, the principal in improving ru>hul mudarris (teacher's soul) acts as a leader/manager, supervisor and coach, and motivator.